Musculoskeletal gearing of the lower extremities across sumaximal loads in weightlifting - Kipp, K.; Harris, C. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to determine if an increase in lift weight is associated with an increase in the effective mechanical advantage (EMA) of the lower extremity joints. Five weightlifters performed cleans at 65, 75, and 85% of their 1-repetition maximum while a motion analysis system and a force plate were used to calculate net joint impulse and EMA of the hip, knee, and ankle extensor muscle groups. The EMA differed significantly between lift loads. As lift weight increased, EMA of extensor muscles also increased. The increase in EMA may allow lifters to generate greater ground reaction forces without a concomitant increase in the net joint impulse. This would suggest an increase in lift weight is, at least, partially associated with an increase in efficiency in the dynamic gearing of the lower extremities.